2005
DOI: 10.1128/mcb.25.24.10791-10802.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Neurogenesis in JNK1-Deficient Embryonic Stem Cells

Abstract: The JNKs are components of stress signaling pathways but also regulate morphogenesis and differentiation. Previously, we invoked a role for the JNKs in nerve growth factor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 43 publications
7
38
0
1
Order By: Relevance
“…Furthermore, different JNK gene knockout mice showed that JNK1 and JNK2 regulate fibroblasts, macrophages, and T cells differently (163,183,184) and also influence skin wound repair differently (185). Neurogenesis in vitro also primarily requires JNK1, but not JNK2 or JNK3 (186). Maintenance of metabolic homeostasis required both JNK1 and JNK2, but JNK1 played more important roles (187).…”
Section: Comparison Of Jnk1 and Jnk2 Functions In Vivomentioning
confidence: 99%
“…Furthermore, different JNK gene knockout mice showed that JNK1 and JNK2 regulate fibroblasts, macrophages, and T cells differently (163,183,184) and also influence skin wound repair differently (185). Neurogenesis in vitro also primarily requires JNK1, but not JNK2 or JNK3 (186). Maintenance of metabolic homeostasis required both JNK1 and JNK2, but JNK1 played more important roles (187).…”
Section: Comparison Of Jnk1 and Jnk2 Functions In Vivomentioning
confidence: 99%
“…Further experiments will be required to support the proposed pathway leading to effects on dendritic architecture through microtubule-associated protein 2 phosphorylation by JNK. However, JNK1 has now been implicated in the dendritic architecture of the cerebellum and motor cortex (28), in addition to maintaining normal brain axonal growth (51) and contributing to the repression of Wnt (Wnt-4 and Wnt-6) expression and neural differentiation (as recently modeled in embryonic stem cells) (10). It is therefore possible that a complex range of JNK1 substrates regulates these biological processes in vivo.…”
Section: Jnk Interaction With and Phosphorylation Of Microtubuleassocmentioning
confidence: 99%
“…Indeed, growing literature supports a role of JNK in cell proliferation, survival, and differentiation. For instance, it was shown that JNK1 and the JNK pathway-specific scaffold protein, JSAP1, promote neural differentiation of embryonic stem cells [45,46]. Activated JNK may also foster axonogenesis and neuronal polarization by targeting cytoskeletal proteins, such as the Tau protein [47,48].…”
Section: Mir-124 Nps Promote Axonogenesismentioning
confidence: 99%